ANALISIS KARAKTERISTIK VEGETATIF DARI EMPAT VARIETAS PADI DALAM PERLAKUAN CEKAMAN KEKERINGAN [Vegetative Characteristics Analysis of Four Rice Varieties Under Drought Stress] - Puspitaningrum, Hardini; Salamah, Andi (Berita Biologi, 2023)
Rice plants that are resistant to drought stress and can be grown on dry land, are needed to increase national food security. A method which has been widely used to determine drought tolerance levels of plants is the morphological analysis. The vegetative characteristics analysis of rice varieties thought to be drought-tolerant, such as West Sumba rice varieties (Pare Lambem and Pare Bakato Kaka), INPARI 32 and INPARI 42, is known to have never been done before. This study aims to identify rice varieties that show the highest stress tolerance based on vegetative performance data through drought stress treatments. The research started with germinating seeds in two treatments (control and PEG 6000 20%) for seven days. The germinated seeds were then transferred to the planting medium and watered every three days for samples treated with PEG 6000 20% after 14 DAP (drought treatment). The vegetative performance data was then processed statistically by calculation of the Fernandez index (1993) or the t-test (α<0.05). The results showed that the percentage of germination, radicle weight, and the average number of leaves (35 DAP) in each variety grouped into the tolerant category. For the leaf curvature scores, the Pare Lambem variety is classified into the sensitive category (score 5), while the other three varieties were classified as Tolerant-category (score 1). Plant height and leaf length values at 7 DAP and 35 DAP showed the same pattern as the leaf curvature score that Pare Lambem showed a significant difference between the control and drought treatments based on the t-test (sensitive category). In contrast, other varieties showed a tolerant category. Based on the assessment of several test characteristics, Pare Lambem was classified into the slightly tolerant category (42.8%), while other varieties were classified into the tolerant category (85.7%).